2012
DOI: 10.1016/j.joca.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between mechanically-induced changes in serum cartilage oligomeric matrix protein (COMP) and changes in cartilage thickness after 5 years

Abstract: The results of this study support the hypothesis that a change in COMP concentration induced by a mechanical stimulus is associated with cartilage thinning at 5 years. Mechanically-induced changes in mechano-sensitive biomarkers should be further explored in the context of stimulus-response models to improve the ability to assess OA progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(153 citation statements)
references
References 42 publications
14
139
0
Order By: Relevance
“…In accordance with our findings, Berry et al reported that in a group of subjects with knee OA followed for 2 years, changes in levels of COMP correlated with medial cartilage volume loss in subjects with lower-than-average COMP levels 29 . In a recent study by ErhartHledik et al, changes in serum COMP observed after a 30-min walk were correlated with cartilage thickness in the medial femur and tibia over a 5-year period indicating that the mechanical stimulus could better delineate cartilage undergoing increased degradation 37 .…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with our findings, Berry et al reported that in a group of subjects with knee OA followed for 2 years, changes in levels of COMP correlated with medial cartilage volume loss in subjects with lower-than-average COMP levels 29 . In a recent study by ErhartHledik et al, changes in serum COMP observed after a 30-min walk were correlated with cartilage thickness in the medial femur and tibia over a 5-year period indicating that the mechanical stimulus could better delineate cartilage undergoing increased degradation 37 .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, monitoring biomarkers is important for early prevention and treatment of OA before significant articular cartilage damage or imaging changes occur (Halász et al, 2007;Koskinen et al, 2011). Research has revealed that a variety of matrix metalloproteinases and cytokines are involved in articular cartilage destruction, which arises from a complex network of factors rather than from a single cause (Li et al, 2011;Erhart et al, 2012). MMP-3 is a protease that can degrade the cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 19 used COMP as a surrogate biological component with a 30 minute walk as the mechanical component and cartilage change over 5 years as the structural component and thus reduced the conceptual systems model (Figure 1) to a practical framework with measurable components. The model was then used in a stimulus-response framework where the mechanical component (30 minute walk) was used to stimulate a biological response (change in COMP concentration from resting) with the structural component (cartilage thickness change over 5 years) investigated as the outcome.…”
Section: New Approaches To the Early Detection Of Oamentioning
confidence: 99%